2020
DOI: 10.1186/s13063-020-04253-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a short-term residential smoking cessation therapy versus standard outpatient group therapy (‘START-Study’): study protocol of a randomized controlled trial

Abstract: Background: In Germany, evidence-based outpatient smoking cessation therapies are widely available. Long-term abstinence rates, however, are limited. Studies suggest that short-term residential therapy enables a higher level of environmental control, more intense contact and greater support among patients and from therapists, which could result in higher abstinence rates. The aim of the current START-study is to investigate the long-term efficacy of a short-term residential therapy exclusively for smoking cess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 80 publications
0
5
0
1
Order By: Relevance
“…An examination of the success rates for the period of four weeks to six months shows that participants in the residential 4-night 5-day program group had the highest success rates. Prior studies have also shown that smokers who participated in the residential smoking cessation program continue to have longer smoking cessation effects than smokers who have experienced other programs [ 23 ]. A previous study also demonstrated that a residential smoking cessation program is effective for heavy smokers who are highly dependent on nicotine [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…An examination of the success rates for the period of four weeks to six months shows that participants in the residential 4-night 5-day program group had the highest success rates. Prior studies have also shown that smokers who participated in the residential smoking cessation program continue to have longer smoking cessation effects than smokers who have experienced other programs [ 23 ]. A previous study also demonstrated that a residential smoking cessation program is effective for heavy smokers who are highly dependent on nicotine [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…These are results from a pilot study. For healthy smokers, results from a larger prospective, randomized and controlled study will be available in late 2022 15 . These two studies will provide a good basis for implementing a larger, controlled study in CD patients in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Die Therapieform wurde in einer Pilotstudie (n = 20) erfolgreich mit dem Ergebnis einer kontinuierlichen 6-Monats-Abstinenzquote von 50 % erprobt [27]. Eine randomisiert-kontrollierte Studie zum Wirksamkeitsvergleich anhand der kontinuierlichen 12-Monats-Abstinenzquoten (biochemisch validiert) mit einer leitliniengemäßen ambulanten Raucherentwöhnungstherapie befindet sich in der Auswertungsphase [29] (Stand 01/2022).…”
Section: Merksatzunclassified